Genitourinary Fistula Experience in a Peripheral Hospital of Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Genitourinary fistula is one of the most dreadful complications encountered in obstetrics and gynaecology and constitute a major surgical challenge for the urogynecologist. With advanced obstetric care, this fistula  is rare in industrialized world but it is still a major health  problem in underdeveloped countries, particularly in sub- Saharan Africa and Asia including Bangladesh. Victim of fistula become physically cripple, socially outcast,  psychologically traumatized. Surgical repair is the definitive  cure. A surgeon with adequate training and experience can optimize outcome of surgery by modifying techniques.  Repair of vesicovaginal fistula remains a major challenge  to surgeon worldwide. Aim of the study was to undertake a baseline evaluation of all genitourinary fistula cases and to share the experience  of management of fistula with others.  This descriptive study was conducted in the department of Obstetrics and Gynaecology, Sylhet M.A.G. Osmani MedicalCollege Hospital. A total 311 genitourinary fistula cases were admitted and managed here from July 2004 to March  2010. In this study 64.63% of the patients were between 20-35yrs of age (range 18-70yrs), 42.76% were primipara whereas 20.57% were grandmulti. Height was